Effect Of Carbonated Beverage And Flouride Mouth Rinses On Enamel Surface And Shear Bond Strength Of Conventional Resin Based Orthodontic Adhesive Composite - Slimani, Abdelbasset Blqasim al-Taib (2012)
Carbonated beverages contains high amount of sugar and acids that can affect the oral health negatively. There were some indications about the erosive effect of acidic mouth rinses on enamel surface. This study was conducted to determine the long term consumption of carbonated beverage and use of fluoride mouth rinses on enamel surface and shear bond strength of conventional resin based orthodontic adhesive composite. An in vitro study was done on 180 extracted human teeth. The brackets were bonded on the teeth with Transbond XT orthodontic adhesive. The teeth were divided randomly and equally into six groups. 25 days exposure cycles were done for all groups as following: group 1 control (distilled water), group 2 (Coca Cola), group 3 (Colgate mouth rinse), group 4 (Oral-B mouth rinse), group 5 (Coca Cola plus Colgate mouth rinse) and group 6 (Coca Cola plus Oral-B mouth rinse). Image analyzer was used and the percentage of enamel decalcification surface area was calculated to evaluate enamel decalcification. Universal test machine was used to determine shear bond strength. Image analyzer was also used for calculating adhesive remnant index on enamel surface after debonding.